2014
DOI: 10.1002/pc.23166
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent cellulose fibers modified with cerium fluoride doped with terbium particles

Abstract: This article describes UV-active cellulose fibers obtained by dry-wet spinning method. The fibers have been formed from an 8% by weight cellulose solution in N-methylomorpholine-N-oxide (NMMO) modified by Ce 0.85 Tb 0.15 F 3 nanocrystals. The modifier was synthesized by wet chemical method, coprecipitation approach. The host was chosen as the most promising one for the green emitting Tb 31 ions. Photoluminescent nanoparticles were introduced into the polymer matrix during the process of dissolving cellulose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The results presented in this paper are the continuation of previous works (Kulpinski et al 2012a, b;Kulpinski et al 2016) which focused only on obtaining the cellulose fibres with various luminescent inorganic modifiers. In the next step the obtained luminescent fibres are introduced to the paper pulp to produce functionalized material.…”
Section: Introductionsupporting
confidence: 80%
“…The results presented in this paper are the continuation of previous works (Kulpinski et al 2012a, b;Kulpinski et al 2016) which focused only on obtaining the cellulose fibres with various luminescent inorganic modifiers. In the next step the obtained luminescent fibres are introduced to the paper pulp to produce functionalized material.…”
Section: Introductionsupporting
confidence: 80%
“…Thanks to the effect of admixture with adequately chosen lanthanide (Ln 3þ ) ions, the materials based on RE fluorides can be an alternative to the currently used phosphors [9]. REF 3 can be used in optoelectronics for construction of optic fibres and amplifiers of optical signals and are promising materials for lasers and in some areas of medicine, especially in bioimaging [10e13].…”
Section: Introductionmentioning
confidence: 99%
“…The XRD patterns of the samples under study showed the set of diffraction peaks related with X-ray scattering on the MCC lattice in the range 10-45 • of 2θ [45,51,52]. These relatively wide intensive peaks are located at 16, 22.5, and 34.5 • of 2θ.…”
Section: Xrd Analysismentioning
confidence: 94%
“…Due to their mechanical flexibility they can be useful in manufacturing of the electronic and opto-electronic devices (solar cells, super-capacitors, lithium-ion batteries, "paper" electronics [38][39][40], luminescence sensors [41][42][43]). Incorporated with luminescent oxides cellulose based composites have shown their importance as advanced optical materials [44][45][46][47]. That is why the second part of this work is devoted to results of our own study of cellulose matrix micro/nanocomposite (CMM/NC) containing luminescence inorganic oxide micro/nanoparticles.…”
Section: Cellulose Matrix Micro/nanocomposites Embedded With Inorganimentioning
confidence: 99%